Urban Greening and Pollen Allergy: Balancing Health and Environmental Sustainability - Stevanovic, Katarina; Sinkkonen, Aki; Pawankar, Ruby; Zuberbier, Torsten (Elsevier, 2025)
rban living requires a careful balance between human health and environmental sustainability when selecting urban vegetation. Public gardens and green roofs offer significant environmental benefits, including air filtration, exposure to health-associated microbiota, and mitigation of the urban heat island effect. However, prioritizing allergy-friendly species is crucial to prevent the exacerbation of pollen allergies. This review highlights 3 primary criteria for selecting vegetation that supports these ecosystem services while minimizing allergy risks. First, reducing the use of many wind-pollinated plants, such as birch trees and grasses, is crucial due to their high pollen production and cross-reactivity with other species, which can exacerbate allergies. In contrast, insect-pollinated plants are generally safer for allergy sufferers. Secondly, cultivating multispecies plant communities with minimal maintenance supports habitats for microbiota and invertebrates, further providing ecosystem services. Lastly, balancing plant gender ratios in urban spaces can help control pollen levels. Together these criteria provide a framework for urban planners to create green spaces that are both environmentally beneficial and allergy friendly. Although this review focuses on European data, the principles discussed have global relevance, reinforcing the need to integrate environmental sustainability with public health considerations in urban planning. Future studies should also investigate the health impacts of plant volatile emissions, explore heat-resistant plant varieties, and assess the ecological risks of invasive species to support sustainable, allergy-friendly urban environments.
Keywords: environmental sustainability; pollen; immune health; ecosystem services; allergy; asthma